VERTEBRAL ARTER DİSEKSİYONLU BİR İNME OLGUSUNDA İNTRAARTERYAL TROMBOLİTİK TEDAVİ - DEĞİRMENCİ, Nilay; NAZ YENİ, Seher; KOÇER, Naci; IŞLAK, Civan; KARAAĞAÇ, Naci (Cerrahpaşa Medical Journal, 2014)
Background.-The importance of dissections in young stroke patients have been emphasized currently. Carotis artery dissections are more frequent than the vertebral artery. The clinical picture of vertebrobasilar artery dissections is one of an occlusion of intracranial arteries. In this article, the clinical features and evaluation of a young stroke patient due to vertebral artery dissection and the value of intraarterial thrombolytic therapy has been debated. Observation.-Fortytwo years old male patient was brought to emergency room. The patient had clinical features of a sudden onset brain stem dysfunction. An early CT scan revealed a hyperdensity over the basilar artery suggestive of a basilar artery trombosis. In order to find out the etiology and to treat this young onset stroke patient, an angiography was performed revealing a vertebral artery dissection and a basilar artery trombosis secondary to this dissection. Three hours after the insult, he was treated with intraarterial urokinase. An early recovery was observed.